Motivating Employees and Organizations to Adopt a Cybersecurity-Focused Culture (Journal of Organizational Psychology, 2021)
We explore the reality of cyber risk faced by organizations, along with the lack of preparedness that continues to become apparent with each successful cyber-attack. Sources project continued growth and evolution of cyber-attacks; they will become more frequent and more sophisticated. To prepare for and mitigate these risks, we propose creating a cybersecurity-focused culture throughout all organizations. The greatest vulnerability, the employees, can also become the greatest defense when properly trained and informed. We review numerous studies that provide outcomes focused on enhancing cybersecurity culture to provide a list of recommended activities for organizations looking to strengthen their cybersecurity posture.
Keywords: organizational psychology; cybersecurity, culture, employee motivation, cybersecurity training